PRAGMATISME PENYELENGGARAAN IBADAH HAJI DI INDONESIA - Muhammad Nuri (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Pragmatism of Hajj in Indonesia. Haji interpreted as an intention to do something honorable. While according to Islamic law is the intention of visiting a particular place (the House of al-Haram and Arafat) at a particular time (in the months of Shawwal) to perform certain deeds are standing at Arafat, Tawaf, sa'ī by certain conditions. As for the maintenance from time to time carried by various groups. During the reign of the Dutch East Indies was conducted by an independent maintenance of the Hajj. However, there are many interest in some quarters, maintenance of the Hajj taken over by the government. Similarly, during the reign of the Republic of Indonesia, a lot of interest happens until finally the government established under the direct authority Directorate of General of Islamic Community Guidance and Hajj Maintenance of Religious Affairs. Keyword: Pragmatism, Hajj Maintenance Abstrak: Pragmatisme Penyelenggaraan Ibadah Haji di Indonesia. Haji diartikan sebagai berkehendak untuk melakukan sesuatu yang dimuliakan. Sedang menurut syara’ ialah niat mengunjungi tempat tertentu (Baitullah al-Haram dan Arafah) pada waktu yang tertentu (pada bulan-bulan Shawal) untuk melaksanakan segala amalan yang tertentu yaitu wuquf di Arafah, tawaf, sa’i dengan syarat tertentu. Adapun penyelenggaraannya dari masa ke masa dilakukan oleh berbagai kalangan. Pada masa pemerintahan Hindia Belanda penyelenggaraan dilakukan bebas, tetapi karena kepentingan beberapa kalangan diambil alih oleh pemerintah. Begitu pula pada masa pemerintahan Republik Indonesia, banyak kepentingan yang berjalan hingga akhirnya pemerintah menetapkan kewenangannya langsung di bawah Direktorat Jenderal Bimbingan Masyarakat Islam dan Penyelenggaraan Haji Kementerian Agama. Kata Kunci: Pragmatisme, Penyelenggaraan HajiDOI:10.15408/sjsbs.v1i1.1532